2015
DOI: 10.2112/si73-098.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Using Cemented Soil-Tire Chips Mixture as Construction Fill: a Laboratory Study

Abstract: Xin, L.; He, J.; Liu, H., and Shen, Y., 2015. Potential of using cemented soil-tire chips mixture as construction fill: A laboratory study.Waste materials that are generated in large quantities, such as waste rubbers, plastics, and dredged soils, can potentially be reused as fill materials in construction projects. It will bring both economical and environmental benefits. This paper firstly presents a review on different methods of reusing scrap tires and waste soils in constructions. Then, a new method of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…With the addition of granular waste rubber pieces to the black cotton soil, it was stated that the compressive strength increased and the swelling pressure decreased according to the triaxial test results [23]. It has been observed that the addition of cement and rubber chips causes an increase in the strength value without joints [24]. After mixing 5%, 10%, and 15% by the weight of pulverized rubber into kaolinite clay, they performed an undrained and drained triaxial test, resulting in 10% crumb.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of granular waste rubber pieces to the black cotton soil, it was stated that the compressive strength increased and the swelling pressure decreased according to the triaxial test results [23]. It has been observed that the addition of cement and rubber chips causes an increase in the strength value without joints [24]. After mixing 5%, 10%, and 15% by the weight of pulverized rubber into kaolinite clay, they performed an undrained and drained triaxial test, resulting in 10% crumb.…”
Section: Introductionmentioning
confidence: 99%